Conceptual aspects, which have influenced on the enshrinement of the right to health in international law - A A Belousova (RUDN Journal of Law, 2014)
The article attempts to determine whether it is possible to find a consensual foundation for the justification of the right to health, as a category of human rights established in International Law. The article focuses on the analysis of the theory of human rights, which is based on the public interest and serves as the conceptual basis of the right to health.